Peer assessment nell$1 (Binsegnamento di Informatica del Corso di Laurea in Medicina e Chirurgia dell$1 (BUniversità di Firenze : Una selezione di elaborati di Informatica Biomedica prodotti dagli studentis - Andreas Robert Formiconi; Maria Renza Guelfi; Marco Masoni; Jonida Shtylla (Firenze University Press, 2019)
This volume explores the issues of using e-learning in university and of developing and using a (3z(Bblended learning(3y (Bteaching method for the course of Computer Science from the first year of the the Medicine and Surgery Degree of the University of Florence. This course was used as a trial for the peer-review teaching method, which can be useful in classes with a high number of students; this publication also includes a selection of the best works produced by the students. The results of the trial prove the advantages of using the peer-review teaching method for other university courses, and the students' works on e-health give current medical practitioners insights on how to use ICT in their practice with skill and care.s